Practical Reporting with Ruby and Rails - Berube, David (Springer, 2017)
Business intelligence and real–time reporting mechanisms play a major role in any of today's forward–looking business plans. With many of these solutions being moved to the Web, the popular Rails framework and its underlying Ruby language are playing a major role alongside web services in building the reporting solutions of tomorrow.